Tingkat Kerentanan Wilayah Pesisir Kota Makassar Terhadap Pencemaran Sampah - Nurmawati Nurmawati; Jonson Lumban Gaol; Marisa Mei Ling (Jurnal Ilmiah Wahana Pendidikan, 2018)
Makassar is one of the major cities in Indonesia with the densest concentration of population in coastal areas so that the pressure on this region is quite high. One of the main problems of Makassar is the existence of trash continues to increase. This study aims to determine the vulnerability level of coastal Makassar against trash pollution. The research was conducted on the Moon from May to July 2015. The research location is the coastal area of Makassar which includes eight subdistricts, namely: Subdistrict Biringkanaya, Tamalanrea, Tallo, Ujung Tanah, Wajo, Makassar, Mariso, and Tamalate. The data used are primary data and secondary data. Primary data collected from surveys and direct observation to the study site while secondary data obtained from the study of literature and related institutions in the city of Makassar. The results showed coastal subdistrict of Makassar city high potential to impact trash pollution. The vulnerability of the coastal area of Makassar against trash pollution are in the high category (very vulnerable).